Simultaneous and rapid colorimetric detection of distinct miRNAs using Split-LAMP - Chua, Yi Jing; Sim, Steven Poh Chuen; Shridharan, Medha; Seow, Yiqi (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Aberrant microRNA (miRNA) expressions are often discovered in many life threatening diseases such as cancer. In particular, recent studies show combinations of miRNA levels have greater diagnostic accuracy as opposed to single miRNA levels. For point-of-care applications, rapid and sensitive isothermal amplification with loop-mediated isothermal amplification (LAMP) has gained significant interest. Method: We developed a cost-effective point-of-care testing (POCT) device for multiple miRNAs that can integrate miRNA signals into a single output. Results and Discussion: We demonstrate that the loop primers for LAMP can be broken and be used for miRNA detection. This split-LAMP approach provides a logic AND-gate output for two distinct miRNA inputs. We then show that this is potentially useable in point-of-care testing using pH-sensitive dye to give a rapid, colorimetric endpoint readout within 30 min. This novel logic gate approach can potentially be extended to multiple miRNAs such that there can be a powerful diagnostic concept for multiple short RNAs in a point-of-care rapid test.